2011
DOI: 10.7863/jum.2011.30.12.1643
|View full text |Cite
|
Sign up to set email alerts
|

First‐Trimester Visualization of the Fourth Ventricle in Fetuses With and Without Spina Bifida

Abstract: Objectives-The purpose of this study was to examine the efficacy of nonvisualization of the fourth ventricle for first-trimester detection of spina bifida.Methods-A total of 250 digitally stored sonographic examinations at gestational ages of 11 weeks to 13 weeks 6 days (245 normal and 5 randomly interspersed spina bifida cases) were retrospectively analyzed by 4 blinded reviewers for the presence or absence of the fourth ventricle followed by an anteroposterior ventricular dimension measurement. The ventricle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 9 publications
0
12
0
1
Order By: Relevance
“…In addition, whether “small intracranial translucency” (measurement <5th percentile) when used as an additional marker would improve the screening efficacy of “absent intracranial translucency” for open spina bifida is uncertain. So far, in several cases of open spina bifida reported in the literature, in which intracranial translucency was determined to be present and a measurement was feasible, the intracranial translucency measurements were within the normal range 3 , 14 …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, whether “small intracranial translucency” (measurement <5th percentile) when used as an additional marker would improve the screening efficacy of “absent intracranial translucency” for open spina bifida is uncertain. So far, in several cases of open spina bifida reported in the literature, in which intracranial translucency was determined to be present and a measurement was feasible, the intracranial translucency measurements were within the normal range 3 , 14 …”
Section: Discussionmentioning
confidence: 95%
“…Chaoui et al 1 , 2 first described intracranial translucency as a useful marker in the detection of open spina bifida at the 11‐ to 13‐week scan, using the midsagittal image of the fetal head and face obtained for nuchal translucency measurement. Subsequently, it has been shown in 2 retrospective studies that normal intracranial translucency had high specificity (98%–99%) for exclusion of open spina bifida, but the sensitivity was only 45% to 50% 3 , 4 . In a retrospective review of images obtained for nuchal translucency measurement, Mangione et al 5 reported that intracranial translucency could be identified in only 52% of normal fetuses, but the visualization rate increased to 85% after specific training of the sonographers.…”
mentioning
confidence: 99%
“…A value < 1 mm can be regarded as abnormal throughout the first trimester screening. According to retrospective studies on the IT in the detection of open spina bifida from, Fong et al, Solt et al, and Mangione et al [4,5,7], detection rates of not more than 50 % can be reached. In our study the sensitivity was 20 % for the absence of the IT and 50 % for a lower cut-off value of 1 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Solt et al . reviewed the stored pictures of 250 fetal examinations containing five abnormal cases for presence or absence of the fourth ventricle, and they observed sensitivity 45% and specificity 98% for detection of NTD …”
Section: Discussionmentioning
confidence: 99%